Hubungan Anemia Dengan Kejadian Perdarahan Postpartum Pada Ibu Bersalin Di Rumah Bersalin Delima Asri Karawang Tahun 2020 - Iga Retia Mufti; Sindi Ayu Lestari (Jurnal Kesehatan Rajawali, 2023)
Data on the prevalence of causes of maternal death in Indonesia are mostly caused by bleeding. The average prevalence of maternal deaths due to bleeding in Indonesia in 2020 is (28.8%). One of the risk factors for postpartum hemorrhage is anemia. Anemia in pregnant women can cause postpartum hemorrhage because low Hb levels can affect the workings of the uterine muscles and result in impaired contractions during labour. The aim of this study was to determine the relationship between anemia and the incidence of postpartum hemorrhage at the Delima Asri Karawang maternity hospital in 2020. This study used an analytical study with a case control approach. The population in this study was 287 mothers giving birth during 2020. The number of case and control samples was made in a 1:1 ratio by following the number of case samples that met the inclusion and exclusion criteria, namely there were 68 case samples and 68 control samples. Bivariate data analysis using the chi square test assisted with SPSS 26 for window. The results of the study showed that mothers with postpartum hemorrhage experienced anemia (85%), mothers without postpartum hemorrhage were not anemic (88.2%). The Chi square statistical test showed that there was a relationship between anemia and the incidence of postpartum hemorrhage with a value (p = 0.000). The conclusion of this study is that there is a relationship between anemia and the incidence of postpartum hemorrhage at the Delima Asri Karawang Maternity Hospital in 2020.